Effect of Penetration Enhancers and Safety on the Transdermal Delivery of Apremilast in Skin - Paulo Sarango-Granda; Lupe Carolina Espinoza; Natalia Díaz-Garrido; Helen Alvarado; María J. Rodríguez-Lagunas; Laura Baldomá; Ana Calpena (MDPI AG, 2022)
The poor water solubility of apremilast (APR) is the main impediment to the penetration of the drug through the skin barrier. The objective of this study was to evaluate the permeability of APR in different solutions enriched with penetration promoters in ex vivo samples of human skin, and additionally assess its tolerance in vivo. To this end, APR solutions with 5% promoter were developed, and the drug's ability to penetrate human abdominal skin samples was evaluated; the coefficients of permeability, cumulated amounts permeated, and flow were some of the parameters evaluated; likewise, the in vitro and in vivo tolerance of the solutions was evaluated. The results obtained showed that the solutions containing squalene as a promoter improved the penetration of APR compared to the other promoters evaluated; in the same way, on an in vitro scale in HaCaT cells, the promoters were not toxic, finding a cell viability greater than 80% at the different dilutions evaluated. In the in vivo tests carried out with the solution that presented the best results (APR-Squalene solution), it was observed that it does not cause irritation or erythema on the skin after its colorimetric and histological evaluation of the dorsal region of rats after its application. Squalene becomes an excellent candidate to improve the permeability of the drug in the case of the development of a topical formulation; in addition, it was confirmed that this penetration enhancer is neither toxic nor irritating when in contact with the skin in in vivo tests.